Developing an integrated multidimensional tax compliance framework: A qualitative study of professional ethics, tax awareness and public trust, good tax governance, the roles of accountants and auditors, and corporate social responsibility - Alvin David P Sitorus; Amelia Azwar; Donna Uli Nainggolan; Indra Pahala (Educoretax, 2026)
This study aims to examine tax compliance determinants from an integrated multidimensional perspective by considering professional ethics, tax awareness and public trust, good tax governance, the roles of accountants and auditors, and corporate social responsibility (CSR). Tax compliance is not merely influenced by economic motivations and regulatory enforcement but is also shaped by ethical awareness, institutional trust, social values, and the need for organizational legitimacy (Pudjono & Rachmania, 2025; Torgler, 2007). This research employs a qualitative case study approach involving individual taxpayers registered at KPP Pratama Bandung, Indonesia. Data were collected through semi-structured interviews, non-participant observations, and document analysis. The data analysis process applied the interactive model developed by Miles et al. (2014). The findings reveal that tax compliance is a complex and multidimensional phenomenon resulting from the interaction of ethical, social, institutional, professional, and legitimacy dimensions. Professional ethics enhances taxpayers’ tax morale, while tax awareness and public trust encourage voluntary tax compliance through greater understanding of tax responsibilities and confidence in taxation institutions, and good tax governance strengthens public trust through transparency, accountability, and service quality. In addition, accountants and auditors play significant roles as professional monitoring mechanisms, while CSR practices support corporate legitimacy and improve relationships with stakeholders (Davis et al., 2016; Suchman, 1995). This study proposes an Integrated Multidimensional Tax Compliance Framework, emphasizing that sustainable tax compliance requires not only regulatory enforcement but also trust, ethical commitment, and effective governance.